SENSOR PVDF DENGAN POLARISASI PERMUKAAN SEBAGAI PENDETEKSI GAYA POTONG PADA MESIN GURDI - Aditya Nugraha; Masri Bin Ardin (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2020)
PVDF sensor is a sensor that is often used to measure force, strain, vibration and heat. In this study, PVDF sensors with surface polarization are used to detect cutting forces on the machine. The PVDF sensor that has been polarized on the surface is placed in the chuck part of the engine. Measuring instrumen for testing and calibrating PVDF sensors is oscilloscope with increased loading and reduced axial and tangential directions. After the calibration process, the PVDF sensor was used to measure cutting force on drilling machine, and then the results were compared with the PCB piezotronics force sensor. The PVDF sensor output signal is measured and studied for its voltage using an oscilloscope, where the output signal is compared to the weight given to the PVDF sensor. From the results of these tests indicate that the maximum deviation in axial loading is 0.32V while the tangential loading is 0.31VKeywords. PVDF sensor, Surface polarization, Drilling machine, Cutting force